YOUTUBE AS A TOOL FOR SELF-DIRECTED LEARNING: ENGLISH EDUCATION STUDENTS' EFFORTS TO IMPROVE THEIR OWN SPEAKING PROFICIENCY - Ate, Christmas Prasetia; Anuno, Agustinho da Conceição (Universitas Negeri Surabaya, 2025)
In the context of digital globalization, this study explores the role of YouTube as a self-directed learning (SDL) tool to enhance speaking proficiency among English Education students at Citra Bangsa University in Indonesia. Recognizing that classroom-based speaking practice is often limited by structural and pedagogical constraints, the research investigates how learners independently engage with YouTube to improve pronunciation, fluency, vocabulary, and confidence. Using a qualitative case study approach, data were collected from the sixth-semester students through semi-structured interviews, reflective journals, and speaking practice logs over a six-week period. Thematic analysis revealed that students employed diverse strategies such as imitation, shadowing, monologue creation, and video-based roleplay, drawing on a wide range of content from educational channels like BBC Learning English to informal vlogs and podcasts. Participants reported increased engagement, language awareness, and motivation. However, they also faced challenges including lack of feedback, difficulty in selecting level-appropriate materials, and digital distractions. Despite these limitations, the overall attitude toward YouTube-based learning was positive, highlighting the platform's potential to supplement formal instruction. The findings suggest that YouTube can serve as an effective tool for promoting learner autonomy and speaking competence when integrated with structured support and digital literacy training. This study contributes to the growing discourse on technology-enhanced language learning and underscores the need for guided self-directed learning models in EFL contexts.